Islamic Cosmology of Accounting: An Introduction - Amelia Indah Kusdewanti (International Journal of Religious and Cultural Studies, 2019)
This article aims to explore new accounting philosophical foundation in the sight of cosmological term. Using literature study this article shows the need of creating that new philosophical term and radically explain the impact toward creation of civilization. The result shows how inadequate accounting philosophical foundation then cause fragmented accounting reality. It also shows us trapped in materialism world and apart from all other aspect, ie sociology, anthropology, as well as religion. Islamic Cosmology of accounting is philosophy of the wholeness built based on Tauhid.